Capcut-assisted Audio Visual Media to Improve Learning Outcomes of IPAS Students in Grade IV Elementary School - Nadirah Nadirah; Kurniana Bektiningsih (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Opinions from students on the IPAS learning content on the material of Indonesia's cultural wealth into prosaic content, which is motivated by the lack of utilization of existing learning media at school, which causes unfocusedness which ultimately leads students to easily bored and less interested in the learning process when the teacher explains the material. To overcome these problems, efforts are needed to develop learning media in audio-visual media assisted by Capcut. This research aims to produce products or audio visual media assisted by Capcut in class IV SDN Wates 02 that are effective and feasible. The type of research used in this study uses the type of R&D (Research and Development) research. The model used in this study uses the ADDIE model, which has five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection was done through observation, interviews, tests, and questionnaires. The subjects used were a team of experts, teachers, and students. Data analysis techniques were conducted through descriptive quantitative data, and qualitative as well as inferential statistics. The results obtained from the media expert team test were 89%, material experts 93%, teachers 95%, and students 95%. The effectiveness results were obtained through pretest and posttest tests, which experienced significant increases from small and large groups. So, the development of audio-visual media assisted by Capcut on the material of Indonesia's cultural wealth is effective and very feasible to use in the learning process and in improving student learning outcomes.